Thyroid neoplasia risk is increased nearly 30 years after the Chernobyl accident. Issue 8 (10th July 2017) - Tronko, Mykola; Brenner, Alina V.; Bogdanova, Tetiana; Shpak, Victor; Oliynyk, Valeriy; Cahoon, Elizabeth K.; Drozdovitch, Vladimir; Little, Mark P.; Tereshchenko, Valeriy; Zamotayeva, Galyna; Terekhova, Galyna; Zurnadzhi, Lyudmila; et al.
Abstract : To evaluate risk of thyroid neoplasia nearly 30 years following exposure to radioactive iodine (I‐131) from the 1986 Chernobyl nuclear accident, we conducted a fifth cycle of thyroid screening of the Ukrainian‐American cohort during 2012–2015, following four previous screening cycles started in 1998. We identified 47 thyroid cancers (TC) and 33 follicular adenomas (FA) among 10, 073 individuals who were <18 years at the time of the accident and had a mean I‐131 dose of 0.62 Gy. We found a significant I‐131 dose response for both TC and FA, with an excess odd ratio per Gy of 1.36 (95% CI: 0.39–4.15) and 2.03 (95% CI: 0.55–6.69), respectively. The excess risk of malignant and benign thyroid neoplasia persists nearly three decades after exposure and underscores the importance of continued follow‐up of this cohort to characterize long‐term pattern of I‐131 risk. Abstract : What's new? Of particular concern following the 1986 accident at the Chernobyl nuclear power plant are long‐term health effects in children and adolescents from the most affected areas who received substantial radiation doses to the thyroid from intake of radioactive iodine (I‐131)‐contaminated milk. To evaluate risk of thyroid neoplasia nearly 30 years following the accident, the authors conducted a fifth cycle of thyroid screening of the Ukrainian‐American cohort during 2012–2015. They found that the excess risk of malignant and benign thyroid neoplasia persists nearly three decades after exposure and underscores the importance of continued follow‐up to characterize long‐term pattern of I‐131 risk.